Genotype classification of Moraxella bovis using MALDI-TOF MS profiles - Olson, Hannah G.; Loy, John Dustin; Clawson, Michael L.; Wynn, Emily L.; Hille, Matthew M. (Frontiers in Microbiology, 2022)
Moraxella bovis (M. bovis) is regarded as a causative agent of infectious bovine keratoconjunctivitis (IBK), the most common ocular disease of cattle. Recently, whole genome sequencing identified the presence of two distinct genotypes within M. bovis that differ in chromosome content, potential virulence factors as well as prophage and plasmid profiles. It is unclear if the genotypes equally associate with IBK or if one is more likely to be isolated from IBK lesions. We utilized 26 isolates of M. bovis that had previously undergone whole genome sequencing and genotype classification to determine the utility of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF) to accurately genotype M. bovis strains. We successfully developed two biomarker models that accurately classified isolates according to genotype with an overall accuracy of 92.9% - 98.9%. These models provide a practical tool to enable studies of genotype associations with disease, allow for epidemiological studies at the sub-species level, and can be used to enhance disease prevention strategies.